Meningkatkan Kesadaran Masyarakat dalam Manajemen Persampahan di Desa Tugu, Kecamatan Sayung, Kabupaten Demak - Thomasonan Lutfie Prananto (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This community service activity aims to increase the awareness of Tugu Village residents of the importance of waste management to create a clean and healthy environment. Tugu Village has experienced changes in land use due to tidal waves and seawater intrusion, resulting in a waste problem that is not properly managed. The methods used in this activity are counseling and demonstration of waste sorting techniques and the creation of temporary disposal sites (TPS). The results of the activity showed an increase in public understanding of waste management and the importance of coordination with local governments in waste management. The sustainability of this program is expected to be realized through cooperation between local governments and universities.